Testing of static synchronous series compensator (SSSC) model in IEEE 9 bus power system network using PSCAD and MATLAB software - Sukma Citra, Jafirin (2010)
Power system capability can be increased by the use of Flexible AC Transmission System devices (FACTS) in transmission systems experiencing high power flows. This thesis presents an analysis of one of these devices, namely, a Static Synchronous Series Compensator (SSSC). Voltage Source Converter (VSC) based FACTS is the most recent approach in FACTS technology. The SSSC is the key series compensation devices that open up new opportunities to control the power on transmission systems in order to enhance their utilization, increase power transfer capability and to improve voltage profile. In order to perform an investigation, an exact model of a 6-pulse GTO converter, is used as the basic building block of SSSC. Then by using a 9-bus test system the effects of SSSC on voltage stability in power systems are examined using MATLAB and PSCAD software. The optimal location of this controller is determined by analyze the lowest bus voltage profile. The 9-bus system parameters such as line voltage, line current, reactive power, Q, and real power, P, transmissions are observed when the SSSC is applied to the system.